O sentido da formação continuada em modelagem matemática na educação matemática desde os professores participantes - Cararo, Elhane de Fatima Fritsch (2017)
Mathematical Modeling has been the focus of research by teachers and researchers dedicated to Mathematics Education; this fact is reflected in numerous publications both in periodicals and in annals of events. However, doing Mathematical Modeling in Mathematical Education implies, in most cases, a change of position on the part of the teacher who needs to conceive Mathematics as a living and dynamic science, the produce of human constructions, interests and social needs. It is evident, therefore, the need to think of continuous training models that provide, for example, a reflection on the pedagogical practices developed and the different possibilities of approaching Mathematical contents. In this direction, there is a project of teacher training in Mathematical Modeling that is developed in several nuclei of the state of Paraná, coordinated by a teacher of the Universidade Estadual do Oeste do Paraná, UNIOESTE, campus of Cascavel. The project proposes to include teachers in an environment where they can review, describe, explore, share and negotiate their personal constructs and their implicit theories, surpassing the existing training models, proving to be an important locus of this research proposal. In this context, we establish our research question: what sense do the participating teachers attribute to the continued formation in Mathematical Modeling in Mathematical Education? It is been refined by the phenomenological vision and requires a study of the object, through the collection of data, understandings and interpretations of the phenomena presented. The data produced for the research were been collected through audio recordings of the training sessions realized every fifteen days at one of the schools in the Municipality of Francisco Beltrão - Paraná, and the collection of testimonies of the teachers participating in the training. For the optimization of the data analysis, we use Atlas.ti software. In the period from October 2015 to July 2016, during the period described in this dissertation, eleven teachers from Elementary School (final years) and High School participated in the training. The research brings contributions to the area of teacher training in Mathematical Modeling, evidencing aspects relevant to what concerns the structure and model of formation, the affective, professional and formative relationships in the continuous formation, the mathematical knowledge of the teacher and the Mathematical Modeling and intends to contribute to the Modeling being disseminated effectively in classrooms, providing a more dynamic and meaningful teaching of Mathematics that searches the critical and social formation of the student through the mathematical knowledge and its relationship with the context lived.